2017
DOI: 10.1021/jacs.7b06597
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Delivery of Proteins by Bioreversible Esterification

Abstract: Cloaking its carboxyl groups with a hydrophobic moiety is shown to enable a protein to enter the cytosol of a mammalian cell. Diazo compounds derived from (p-methylphenyl)glycine were screened for the ability to esterify the green fluorescent protein (GFP) in an aqueous environment. Esterification of GFP with 2-diazo-2-(p-methylphenyl)-N,N-dimethylacetamide was efficient. The esterified protein entered the cytosol by traversing the plasma membrane directly, like a small-molecule prodrug. As with prodrugs, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
143
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 41 publications
3
143
0
4
Order By: Relevance
“…Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs). Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs).…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs). Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs).…”
Section: Introductionmentioning
confidence: 99%
“…[2,4] Therefore, intracellular delivery of functional, native proteins (including antibodies) remains akey challenge in protein-based therapy. [10] Although the delivered cargos were unmodified, their slow endosome escape was not ideal for immediate bioavailability.The noncovalent L17E/cargo formulation also limits the type of proteins that could be used and delivery efficiency.O ff ew reports that showed successful delivery of proteins directly into the cytoplasm of mammalian cells,all of them require genetic and/or chemical modifications to the cargos, [11][12][13] and almost none allows intracellular release of "native" proteins to enable full restoration of their activities. Futaki et al reported an endosomolytic peptide (i.e., L17E) that forms noncovalent complexes with various proteins,l eading to cell entry via endocytosisfollowed by successful cytosolic protein liberation.…”
mentioning
confidence: 99%
“…Upon successful intracellular delivery via CPD-assisted endocytosis-independent pathways, [19] followed by spontaneous GSH-catalyzed depolymerization inside mammalian cells, [14,15] the resulting CPD-free cargo was essential "native" barring minimal changes to the glycan, which was not expected to alter the protein in any noticeable way.I nt he second strategy (named traceless tagging;F igure 1B,b ottom), in order to label non-glycosylated proteins with CPD,t wo cleavable linkers (NBL and TCOL)w ere developed to reversibly label lysines in ap rotein (Step 1). [13] Our traceless approach thus provides an alternative for protein delivery through reversible tagging of lysines instead. [15] Following intracellular delivery (Step 3), the resulting protein complex could undergo GSH-catalyzed disulfide cleavage followed by spontaneous cleavage of the selfimmolative linker, [25] leading to successful release of the "native" protein.…”
mentioning
confidence: 99%
“…Kreuzmetathesereaktionen von Allylcystein oder Allylselenocystein zeichnen sich durch ihre einzigartige Einfachheit und Effektivitäta us,d ie auf die postulierte stabilisierende Interaktion in einem Metallacyclobutanintermediat zurückzuführen sind (Abbildung 19, rechts). [123][124][125] Jahrzehnte später berichteten Francis und Mitarbeiter über die Katalyse einer Modifikation an der Tryptophan-Indol-Seitenkette mit stabilisierten Diazocarbenvorläufern durch einen einfachen Rhodium(II)-Paddlewheel-Carboxylatkomplex [126] (Abbildung 21, 22), was die übliche Bevorzugung unkatalysierter oder kupferkatalysierter Reaktionen vollständig auf den Kopf stellte. Metatheseansätze bedürfen der vorherigen Inkorporation eines Olefinzentrums und fallen dadurch aus dem Fokus dieses Aufsatzes heraus.Ein kürzlich erschienener Übersichtsartikel deckt dieses Thema jedoch tiefgreifend ab.…”
Section: Katalytische Metallcarbenintermediate:a Sp Trp Cys Lysunclassified
“…[133,134] Abbildung 23 stellt die Ergebnisse eines ersten Berichts über das Biotin-Diazokonjugat dar, [133] doch ähnliche Resultate konnten auch durch ein separates Biotinadditiv erzielt werden. [123][124][125] Die Chemie der Metallcarbene ist von komplexen Diazoverbindungen abhängig,w elche oftmals durch Diazotransferprozesse mithilfe eines Azidreagenzes synthetisiert werden müssen. Die Katalysatorkontrolle der Diazo-Spezifitäts tellt eine wertvolle Ergänzung der unkatalysierten Modifikation an Carboxylatseitenketten durch Diazoverbindungen dar.…”
Section: Angewandte Chemieunclassified